An Undiagnosed Case of Hypothalamic Hamartoma with a Rare Presentation - Shervin Badihian; Saeideh Bahrani; Nasim Tabrizi; Houshang Moein; Mohammad Zare; Majid Barekatain; Reza Basiratnia; Elham Rahimian; Amirali Mehvari Habibabadi; Payam Moein; Jafar Mehvari Habibabadi (Case Reports in Medicine)
Background. Hypothalamic hamartomas (HHs) are rare tumor-like malformations that may present with complex partial seizures refractory to anticonvulsants in adulthood. The condition may be misdiagnosed because of rarity. Case Presentation. We report a 25-year-old man with complaint of seizures presented by falling, tonic spasm of limbs, oral automatism, vocalization, and hypermotor activities. His seizures started at the age of one month and presented as eye deviation and upper limbs myoclonic jerk, followed by frequent seizures with variable frequency. The patient had delayed developmental milestones and was mentally retarded. He was hospitalized and underwent video-EEG monitoring and neuroimaging, and the diagnosis of HH was made. The patient became candidate for surgery after that. Conclusion. In this case, the underlying etiology of seizures was diagnosed after 25 years. HH is a rare condition and neurologists may encounter very small number of these cases during their practice. Therefore, they should consider it in patients who present with suspected signs and symptoms.